Epithelial tumors of the lacrimal gland in the Chinese: a clinicopathologic study of 298 patients - Zeng, Jie; Shi, Ji-tong; Li, Bin; Sun, Xian-li; An, Yu-zhi; Li, Liao-qing; Gao, Fei; Xu, Jian-ping; Jonas, Jost B. (Graefe's archive for clinical and experimental ophthalmology, 2010)
To examine the clinicopathologic characteristics and clinical features of epithelial tumors of lacrimal gland in China.